Cryo EM structure of intact rotary H+-ATPase/synthase from Thermus thermophilus - Atsuko Nakanishi; Jun-ichi Kishikawa; Masatada Tamakoshi; Kaoru Mitsuoka; Ken Yokoyama (Nature Communications, 2018)
H+-ATPases employ a rotary catalytic mechanism to couple ATP synthesis/hydrolysis with proton translocation through the membrane. Here, the authors use high-resolution cryoEM to characterize three rotational states of a bacterial H+-ATPase, providing a more detailed model of its catalytic mechanism.